2018
DOI: 10.1111/codi.13965
|View full text |Cite
|
Sign up to set email alerts
|

Back‐to‐back colon capsule endoscopy and optical colonoscopy in colorectal cancer screening individuals

Abstract: CCE is superior to colonoscopy in polyp detection rate and per-patient sensitivity to > 9 mm polyps, but only in complete CCE examinations. The rate of incomplete CCE examinations must be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
89
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 12 publications
3
89
0
1
Order By: Relevance
“…rate of polyps in this group, but only half of the polyps detected by CCE in the patients referred for colonoscopy could be found and removed. In a recent trial on CRC screening patients we found a higher polyp detection rate of 86% in complete exams, and a similar trend of CCE reporting more polyps than colonoscopy [8].…”
Section: Discussionsupporting
confidence: 65%
“…rate of polyps in this group, but only half of the polyps detected by CCE in the patients referred for colonoscopy could be found and removed. In a recent trial on CRC screening patients we found a higher polyp detection rate of 86% in complete exams, and a similar trend of CCE reporting more polyps than colonoscopy [8].…”
Section: Discussionsupporting
confidence: 65%
“…KRK taraması için birçok ülke yaygın olarak GGK, rektosigmoidoskopi ve kolonoskopi kullansa da, kapsül endoskopi ve sanal kolonoskopi gibi kolonu anatomik olarak inceleyen yöntemler veya deneysel aşamada olan plazmada veya gaytada çeşitli DNA ve mikroRNA moleküllerinin araştırılmasına dayanan bazı testlerle ilgili yoğun çalışmalar yapılmaktadır (Tablo 2). 9,10,11,12 Bu testlerin hangisi ya da hangilerinin kullanılacağı ile ilgili standart bir öneri yoktur. Ülkeler kanser görülme sıklığı, tarama yapacak iş gücü, ülkenin ekonomik durumu gibi bazı faktörlere bağlı olarak farklı tarama stratejileri uygulayabilmektedir.…”
Section: Discussionunclassified
“…Colon capsule endoscopy (CCE) is an upcoming new technology [1][2][3], which is being tested for efficacy as an alternative to conventional optical colonoscopy (OC) [2,4], in individuals with immunological fecal occult blood test (FIT), who participate in a colorectal cancer screening program. OC may be experienced as distressing, humiliating and painful, but has the capability of obtaining biopsies or excision of neoplastic lesions [5].…”
Section: Introductionmentioning
confidence: 99%
“…CCE is an examination of the colon and rectum with a camera capsule, during which the person wears a receiver in a belt around the belly [4]. The camera capsule is swallowed and takes multiple pictures, while the capsule passes through the intestine and transmits the recordings to the receiver for further analysis and interpretation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation